Hormesis, cellular stress response, and redox homeostasis in autism spectrum disorders. Issue 12 (19th September 2016) - Calabrese, V.; Giordano, J.; Ruggieri, M.; Berritta, D.; Trovato, A.; Ontario, M.L.; Bianchini, R.; Calabrese, E.J.
Abstract : In the United States, 1.1–1.5% of children have been diagnosed with autism spectrum disorders (ASD), corresponding to a 30% increase in incidence and prevalence. Social and communication impairments are the main signs and symptoms of ASD, and currently available medications have been ineffective in reducing these core deficits. Observational studies have indicated that children with ASD tend to show improved cognition and behavior after febrile illness, which is associated with alteration of metabolic pathways, leading to cellular stress responses and increased expression of heat shock proteins (Hsps). Sulforaphane and hydroxytyrosol, phytochemicals derived from cruciferous vegetables and extra virgin olive oil, respectively, can induce metabolic effects in cellular stress responses that are similar to those produced by fever. Thus, modulation of endogenous cellular defense mechanisms may be an innovative approach for therapeutic intervention in ASD and other disorders associated with neuroinflammation and neurodegeneration. This Review introduces the hormetic dose–response concept and presents possible mechanisms and applications for neuroprotection. We address the emerging role of Hsps in the neuroprotective network of redox stress‐responsive mechanisms and propose the potential therapeutic utility of the nutritional antioxidants sulforaphane and hydroxytyrosol against particular signs and symptoms of ASD. We argue that such research findings must be approached with pragmatism and prudence. It is vital to capitalize on recent and ongoing investments in brain science research and to refine neuroscientific knowledge and capability for more accurate diagnosis and safe, effective, and ethically sound treatment of ASD and other neuropsychiatric spectrum disorders. © 2016 Wiley Periodicals, Inc.